Caring and living with Prader-Willi syndrome in Italy: integrating children, adults and parents' experiences through a multicentre narrative medicine research. Issue 8 (6th August 2020) - Ragusa, Letizia; Crinò, Antonio; Grugni, Graziano; Reale, Luigi; Fiorencis, Alessandra; Licenziati, Maria Rosaria; Faienza, Maria Felicia; Wasniewska, Malgorzata; Delvecchio, Maurizio; Franzese, Adriana; Rutigliano, Irene; Fusilli, Paola; et al.
Abstract : Objectives: Prader-Willi syndrome (PWS) significantly impacts health-related quality of life; however, its relational and existential aspects remain unknown in Italian clinical and social debate. The project aimed to investigate the impact of PWS on illness experience through narrative medicine (NM) to understand the daily life, needs and resources of patients with PWS and their caregivers, and to furnish insights for clinical practice. Design and setting: The project involved 10 medical centres of the Italian Network for Rare Diseases and PWS family associations and targeted underage and adult patients with PWS and their caregivers. Written interviews, composed by a sociodemographic survey and a narrative, were collected through the project's website. Three dedicated illness plots employed evocative and open words to facilitate individual expression and to encourage reflection. Narratives were analysed through NVivo software. Researchers discussed the results with the project's steering committee. Participants: Twenty-one children and adolescents and 34 adults with PWS joined the project, as well as 138 caregivers. A PWS diagnosis or the caregiving of a patient with PWS older than 5 years represented the eligibility criteria, as well as the willingness to share their illness experience by writing and the ability to communicate in Italian. Results: The analysis of narratives led to understanding the PWS social and relational issues concerning diagnosis and current management, PWS daily experiences and social contexts, PWS implications in the working sphere and participants' future perspectives. Narratives demonstrated that PWS management affects relationships and work-life balance and that social stigma remains present. Conclusion: The project represented the first effort to investigate the impact of PWS on illness experience in Italy through NM while considering the perspectives of patients with PWS and their caregivers. The findings indicated that a multiprofessional approach is fundamental to ensure adequate treatment and provided elements for its improvement.